Increasing Adolescent Women's Knowledge of Blood Supplement Tablets through Health Education in Schools: Peningkatan Pengetahuan Remaja Putri tentang Tablet Tambah Darah melalui Edukasi Kesehatan di Sekolah - Rizky Rahayu Putri; Lisnawati Lisnawati; Ismunandar Ismunandar (Salando Health Journal, 2025)
Background: The lack of knowledge among adolescent girls about anemia and the importance of consuming iron tablets is one of the main factors contributing to low compliance with iron supplementation. School-based health education can be an effective intervention to increase adolescents' understanding and awareness of the importance of anemia prevention. Research Objective: To determine the effect of education on improving adolescent girls' knowledge about iron supplement tablets at State High School 4 Palu. Research Method: A Quasi-Experimental design with a pre-test and post-test design was used. The sample consisted of 68 10th-grade female students selected through simple random sampling. The research instrument consisted of a knowledge questionnaire about iron tablets administered before and after the educational intervention using PowerPoint and leaflets. Data analysis was performed using the Wilcoxon Signed-Rank Test. Results: Showed a significant increase in respondents' knowledge levels after education (p < 0.001). Before the intervention, only 14.7% of students had good knowledge, increasing to 69.1% after receiving education. Conclusion: These findings show that health education has a positive effect on increasing adolescent girls' knowledge about iron tablets. A continuous and collaborative health education program needs to be implemented to encourage regular consumption of iron-fortified tablets as a preventive measure against anemia in adolescents.